The Use of Phase Change Materials to Improve the External Walls` Thermal Parameters of Heated Buildings - Nakielska, Magdalena; Kaczmarek, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Currently, it is estimated that the construction sector consumes over 40% of the energy produced and about 50% of the mass of processed materials. As a consequence, there is a challenge to look for alternative material solutions allowing for the storage and conversion of energy. Phase change materials give us such opportunities. Their introduction leads to additional benefits related to thermal parameters.
Keywords: phase change material (PCM); reducing energy consumption; thermal conductivity coefficient; laboratory tests